Bioactive Molecules from Tropical American Plants: Potential Anti-Inflammatory Agents for Cytokine Storm Management - Erika Plazas; Lucellys Sierra-Marquez; Jesus Olivero-Verbel (Molecules)
The cytokine storm, a hyperinflammatory response characterized by the excessive release of pro-inflammatory mediators such as TNFα, INFγ, IL-1β, IL-6, and GM-CSF, has been identified as a critical factor in the progression and severity of acute inflammatory conditions. Regulating these pathways is essential for mitigating systemic damage and improving outcomes. Natural products from tropical American plants have shown significant potential in modulating these hyperinflammatory responses. Key polyphenols, like quercetin and luteolin, found in plants such as Achyrocline satureioides and Mangifera indica demonstrate the downregulation of NF-κB and inhibition of pro-inflammatory cytokines. Alkaloids, such as berberine and mitraphylline, isolated from Berberis species and Uncaria tomentosa, respectively, have shown potent effects in suppressing nitric oxide production and regulating inflammasomes. Terpenoids, including parthenolide from Tanacetum parthenium and curcumol from Curcuma longa, exhibit multitarget activity, reducing cytokine levels and inhibiting key inflammatory enzymes like COX-2 and iNOS. These findings highlight the immense potential of bioactive compounds from tropical American plants as modulators of immune–inflammatory pathways, providing a foundation for developing effective therapeutic agents to counteract the severe effects of cytokine storms.